Virulence Plasmid Diversity in Clostridium perfringens Type D Isolates - Sayeed, Sameera (American Society for Microbiology, 2007)
Clostridium perfringens type D isolates are important in biodefense and also cause natural enterotoxemias in sheep, goats, and occasionally cattle. In these isolates, the gene (etx) encoding ɛ-toxin is thought to reside on poorly characterized large plasmids. Type D isolates sometimes also produce other potentially plasmid-encoded toxins, including C. perfringens enterotoxin and beta2 toxin, encoded by the cpe and cbp2 genes, respectively. In the current study we demonstrated that the etx, cpe, and cpb2 genes are carried on plasmids in type D isolates and characterized the toxin-encoding plasmids to obtain insight into their genetic organization, potential transferability, and diversity. Southern blotting of pulsed-field gels showed that the etx gene of type D isolates can be present on at least five different plasmids, whose sizes range from 48 to 110 kb. The etx plasmids also typically carried IS1151 and tcp open reading frames (ORFs) known to mediate conjugative transfer of C. perfringens plasmid pCW3. PCR studies revealed that other than their tcp ORFs, etx plasmids of type D isolates do not carry substantial portions of the conserved or variable regions in the cpe plasmids of type A isolates. Southern blotting also demonstrated that in type D isolates the cpe and cpb2 genes are sometimes present on the etx plasmid. Collectively, these findings confirmed that the virulence of type D isolates is heavily plasmid dependent and indicated that (i) a single type D isolate can carry multiple virulence plasmids, (ii) a single type D virulence plasmid can carry up to three different toxin genes, and (iii) many etx plasmids should be capable of conjugative transfer.